Molecular epidemiology and antibiotic resistance of Burkholderia pseudomallei isolates from Hainan, China: A STROBE compliant observational study - Rao, Chenglong (Medicine (Baltimore), 2019)
Burkholderia pseudomallei is the causative agent of meliodosis, and the cases in China are gradually increasing. The present retrospective study aimed to surveil the molecular epidemiological characteristics and antibiotic resistance of B pseudomallei isolates. B pseudomallei strains were isolated and verified from meliodosis patients with relevant epidemiological information from 2004 to 2016 in Hainan, China. Pulsed-field gel electrophoresis based on Spe I digestion was carried out, and antimicrobial resistance of B pseudomallei strains was observed against 9 frequently-used antimicrobials. A total of 164 B pseudomallei isolates were successfully divided into 60 pulsed-field gel electrophoresis (PFGE) patterns, including 33 clusters and 27 single types, at an 85% similarity level. The isolates also exhibited a high level of ceftazidime resistance rate (12.8%, 21/164). B pseudomallei strains were mainly heterogenous with no predominant type, but there were some clonal populations, dominate clusters prevalent and the resistance rates of cephems antimicrobial increased significantly between 2004 and 2016 along with the number of melioidosis cases collected in Hainan (cefoperazone-sulbactam [SCF], r(s) = 0.96, P = .04; ceftazidime [CAZ], r(s) = 0.98, P = .01). In conclusion, this study will help to enhance our understanding of molecular characteristics and antibiotic resistance of B pseudomallei.